The hospital outcomes compared between the early and late hypothermia-treated groups in neonates. (17th July 2016) - Youn, Young-Ah; Kim, Ji Hoon; Yum, Sook-Kyung; Moon, Cheong-Jun; Lee, In-Goo; Sung, In Kyung
Abstract: Background and objective : The incidence of hypoxic ischemic encephalopathy (HIE) in developed countries is estimated to be 1.5 per 1000 live births. The primary aim of this study was to analyze whether earlier hypothermia (≤1 h) improves hospital outcomes in survivors who underwent therapeutic hypothermia (TH) when compared with late TH (>1 h). Method : Forty-nine (70%) newborns received TH for 72 h, within 6 h of birth; the remaining 21 received standard care. We divided the TH-treated newborns into early and late groups; early cooling was considered when TH was started ≤1 h after birth; late cooling was considered when started >1 h. Results : The early TH group consisted of 20 of 49 (41%) infants; the late TH group consisted of 29 (59%) infants. Apgar score at 1 min and the initial calcium level was significantly lower in the early (≤1 h) TH infants; there were significantly more inborns in the early TH group ( p  = 0.008). Infants in the late TH group manifested more clinical seizures followed by more abnormal EEG findings, longer ventilator care and longer hospitalization ( p  = 0.001). TH-related complications and mortality were not significantly different between the two groups. Conclusions : Early TH (≤1 h) had lower Apgar score at 1 min and initial calcium level, but had decreased incidence of clinico-electrical seizures among HIE infants. Also, ventilator support and hospitalization period were longer in the late TH group.